Vertical Collusion And Re-Running Tender: A Study Of The Decision Of The Indonesian Business Competition Supervisory Commission (KPPU) NO: 17/KPPU-L/2022 - Parulian Panjaitan, Mardongan; Imam Haryanto; Iwan Erar Joesoef (CV. AFDIFAL MAJU BERKAH, 2024)
This study was conducted to analyze the Business Competition Supervisory Commission's consideration of re-tendering as a vertical conspiracy, as well as to examine arrangements for the application of re-tendering that provide legal certainty for project owners and tender participants. This research uses qualitative normative methods involving steps such as statutory studies, case studies, and conceptual approaches. This research uses a statutory approach to examine related regulations, a case approach to analyze decisions related to tender conspiracy, and a conceptual approach to understand relevant legal ideas and concepts. The results showed that the Business Competition Supervisory Commission (KPPU) concluded that there was a tender conspiracy in the process of canceling and re-running the tender by PT Jakarta Propertindo (Perseroda). Where PT Jakarta Propertindo (Perseroda) is a company officially assigned by the Provincial Government of DKI Jakarta to plan, build, manage, and maintain the Jakarta Arts Center Taman Ismail Marzuki. The Commission Panel found that the Reported Party I, which canceled the tender without a valid reason and could not be accounted for, deliberately did so to facilitate the Reported Party II and the Reported Party III to win the tender. Changes in the assessment procedures, especially in the experience aspect of the technical assessment, proved the intent of the Procurement Team to increase the technical scores of the Reported Party II and the Reported Party III. Thus, it confirms the role of KPPU in prohibiting vertical conspiracy and re-tendering in the practice of goods and services procurement, which provides legal certainty for project owners and tender participants